Pengaruh Kepemimpinan Transformasional dan Motivasi Terhadap Kepuasan Kerja Karyawan - Hardiyani, Rini; Al Ardi , Aditya Nizar; Malik, Amalia; Universitasari, Pascawati Savitri (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the effect of transformational leadership and motivation on employee job satisfaction. The sample used in this study was 30 employees at Catering Umik in Jember. The independent variables in this study used were transformational leadership and motivation while the dependent variable was job satisfaction. This study used quantitative descriptive analysis by taking questionnaires from existing samples. This study uses a likert interval scale of 1-5. The data processing method in this study uses SPSS software. It can be concluded that the results are; 1) transformational leadership has a significant effect on job satisfaction. 2) Motivation does not have a significant effect on job satisfaction. 3) Transformational leadership and motivation simultaneously have a significant effect on job satisfaction.